Seroprevalence of cytomegalovirus antibodies in blood donors in southern, Brazil - Souza,Marli Adelina (2010)
INTRODUCTION: Cytomegalovirus (CMV) infection is a matter of concern for blood bank professionals and blood transfusion recipients, especially in cases of transfusions to neonates and immunocompromised patients. Thus, the present study aimed to determine the seroprevalence of CMV IgG and IgM antibodies among blood donors in the city of Lages, in the mountain region of Santa Catarina, southern Brazil, and to investigate possible associations between the socioeconomic characteristics of donors and CMV serological status. METHODS: A seroepidemiological cross-sectional study was conducted on 1,045 blood samples from donors that were used in serological screening over a one-year investigation. All the analyses were conducted using the microparticle enzyme immunoassay with Biokit® reagents (Barcelona, Spain), in accordance with the manufacturer's instructions. RESULTS: Anti-CMV IgG seroprevalence in the sample studied was 96.4% (95% CI: 95.23 - 97.50) and that of anti-CMV IgM was 2.3% (95% CI: 1.39 - 3.20). There were no statistically significant associations between the presence of antibodies and the socioeconomic characteristics of donors. CONCLUSIONS: The blood donors in the study region had high seroprevalence of anti-CMV IgG. Thus, blood component screening strategies and careful indication for blood transfusions require special attention among healthcare professionals as part of the actions for prevention and reduction of primary infections caused by CMV.